2021
DOI: 10.1016/j.dcn.2021.100985
|View full text |Cite
|
Sign up to set email alerts
|

Happy for Us not Them: Differences in neural activation in a vicarious reward task between family and strangers during adolescent development

Abstract: During adolescence social-interactions with other people become more relevant. One key aspect of these interactions is cooperative behavior. Cooperation relies on a set of cognitive and affective mechanisms. In this study, we focused on the mental ability to feel happy for another person’s positive experience, called vicarious joy. We investigated the neural mechanisms of this ability using a false-choice vicarious reward fMRI task. Participants played a game where they could win monetary rewards for themselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 62 publications
0
26
0
Order By: Relevance
“…Nineteen studies reported prosocial neural correlates concurrently with a prosocial decision-making task. Seven of these used the Dictator Game ( Moor et al, 2012 ; Güroğlu et al, 2014 ; Will et al, 2016 , 2018 ; Schreuders et al, 2018 , 2019 ; Duell et al, 2021 ), and five used close variations on the Dictator Game, including either the Allocation Game ( Do and Telzer, 2019 ; Do et al, 2019 ), the Family Assistance Task ( Telzer et al, 2011 , 2013 ), or the Charity of Self Yield Task ( Spaans et al, 2020 ; Brandner et al, 2021 ). The seven remaining studies used various games that also involved resource distribution: the Socially Mindful task ( Lemmers-Jansen et al, 2018 ), the Altruism Antisocial Game ( Sakai et al, 2017 ), the Trust Game ( van den Bos et al, 2009 , 2011 ), the Public Goods Game ( Van Hoorn et al, 2016 ), and Cyberball ( van der Meulen et al, 2016 ; Tousignant et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nineteen studies reported prosocial neural correlates concurrently with a prosocial decision-making task. Seven of these used the Dictator Game ( Moor et al, 2012 ; Güroğlu et al, 2014 ; Will et al, 2016 , 2018 ; Schreuders et al, 2018 , 2019 ; Duell et al, 2021 ), and five used close variations on the Dictator Game, including either the Allocation Game ( Do and Telzer, 2019 ; Do et al, 2019 ), the Family Assistance Task ( Telzer et al, 2011 , 2013 ), or the Charity of Self Yield Task ( Spaans et al, 2020 ; Brandner et al, 2021 ). The seven remaining studies used various games that also involved resource distribution: the Socially Mindful task ( Lemmers-Jansen et al, 2018 ), the Altruism Antisocial Game ( Sakai et al, 2017 ), the Trust Game ( van den Bos et al, 2009 , 2011 ), the Public Goods Game ( Van Hoorn et al, 2016 ), and Cyberball ( van der Meulen et al, 2016 ; Tousignant et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies compared (pro)social decision-making in general (i.e., the deliberation phase) to neutral/non-prosocial control conditions (hereafter, “prosocial decision-making”) ( van den Bos et al, 2011 ; Moor et al, 2012 ; Van Hoorn et al, 2016 ; Sakai et al, 2017 ; Lemmers-Jansen et al, 2018 ; Tousignant et al, 2018 ; Will et al, 2018 ; Duell et al, 2021 ). Eleven studies contrasted prosocial decision-making trials based on the actual prosocial choice such that decision-making with prosocial outcomes were compared to decision-making with non-prosocial outcomes (hereafter, “prosocial choices”) ( Telzer et al, 2011 , 2013 ; Güroğlu et al, 2014 ; Lemmers-Jansen et al, 2018 ; Schreuders et al, 2018 , 2019 ; Do and Telzer, 2019 ; Do et al, 2019 ; Spaans et al, 2020 ; van der Meulen et al, 2016 ; Brandner et al, 2021 ). Twelve studies analyzed neural activation during prosocial decision-making that correlated with the frequency of making prosocial choices, and therefore accounts for between-person differences (hereafter, “giving frequency” or “behavior frequency”) ( van den Bos et al, 2009 , 2011 ; Masten et al, 2010 ; Moor et al, 2012 ; Güroğlu et al, 2014 ; Overgaauw et al, 2014 ; Will et al, 2016 ; Schreuders et al, 2018 ; Tashjian et al, 2018 ; Tousignant et al, 2018 ; Ferschmann et al, 2019 ; Okada et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on adolescent development has often focused on aspects with negative reallife outcomes, including elevated risk-taking and sensation seeking (Braams et al, 2015;Galvan et al, 2006;Harden and Tucker-Drob, 2011;Romer and Hennessy, 2007), but positive aspects have become evident more recently, too (DePasque and Galván, 2017;Sercombe, 2014). For example, adolescents have outperformed adults in certain measures of creativity (Kleibeuker et al, 2013) and showed enhanced social learning (Brandner et al, 2021;Gopnik et al, 2017) and exploration (Somerville et al, 2017). With particular interest to our hypothesis, adolescents have outperformed adults on stochastic learning tasks (Cauffman et al, 2010;Davidow et al, 2016) and some aspects of a reversal-learning task (van der Schaaf et al, 2011;Fig.…”
Section: U-shapes In Developmentmentioning
confidence: 89%